Electrochemical monitoring of ROS generation by anticancer agents: the case of chartreusin. Issue 71 (21st September 2017) - Doménech-Carbó, Antonio; Cebrián-Torrejón, Gerardo; Montoya, Noemí; Ueberschaar, Nico; Scotti, Marcus Tullius; Benfodda, Zohra; Hertweck, Christian
Abstract : Generation of ROS by anticancer agents is monitored using solid state electrochemical techniques. Abstract : Solution phase and solid-sate electrochemical techniques centered in the voltammetry of microparticles approach are applied for testing the cytotoxic activity of anticancer drugs. The possibility of electrochemical generation of reactive oxygen species (ROS) is exploited for evaluating their contribution to cellular damage. The described methodology is applied to the case of chartreusin (Ch) whose electrochemistry in non-aqueous solutions and in the solid state in contact with aqueous electrolytes is described in the absence (experimental data were confirmed by theoretical calculations) and in the presence of double-stranded DNA (dsDNA). In parallel, scanning electrochemical microscopy (SECM) examination of dsDNA fibers was developed. Electrochemical data suggest that Ch-induced dsDNA interaction can operate by a two pathways: via intercalation and by mechanisms related with ROS generation. Although reduced Ch forms electrochemically generated can act as radical scavengers blocking the ROS generation chain, this property is interrupted upon binding to dsDNA.